let Q be Quantum_Mechanics; :: thesis: for p, q being Element of Prop Q holds
( p <==> q iff for s being Element of Sts Q holds (Meas ((p `1),s)) . (p `2) = (Meas ((q `1),s)) . (q `2) )

let p, q be Element of Prop Q; :: thesis: ( p <==> q iff for s being Element of Sts Q holds (Meas ((p `1),s)) . (p `2) = (Meas ((q `1),s)) . (q `2) )
thus ( p <==> q implies for s being Element of Sts Q holds (Meas ((p `1),s)) . (p `2) = (Meas ((q `1),s)) . (q `2) ) :: thesis: ( ( for s being Element of Sts Q holds (Meas ((p `1),s)) . (p `2) = (Meas ((q `1),s)) . (q `2) ) implies p <==> q )
proof
assume A1: p <==> q ; :: thesis: for s being Element of Sts Q holds (Meas ((p `1),s)) . (p `2) = (Meas ((q `1),s)) . (q `2)
let s be Element of Sts Q; :: thesis: (Meas ((p `1),s)) . (p `2) = (Meas ((q `1),s)) . (q `2)
q |- p by A1;
then A2: (Meas ((q `1),s)) . (q `2) <= (Meas ((p `1),s)) . (p `2) ;
p |- q by A1;
then (Meas ((p `1),s)) . (p `2) <= (Meas ((q `1),s)) . (q `2) ;
hence (Meas ((p `1),s)) . (p `2) = (Meas ((q `1),s)) . (q `2) by ; :: thesis: verum
end;
assume A3: for s being Element of Sts Q holds (Meas ((p `1),s)) . (p `2) = (Meas ((q `1),s)) . (q `2) ; :: thesis: p <==> q
thus p |- q by A3; :: according to QMAX_1:def 11 :: thesis: q |- p
let s be Element of Sts Q; :: according to QMAX_1:def 10 :: thesis: (Meas ((q `1),s)) . (q `2) <= (Meas ((p `1),s)) . (p `2)
thus (Meas ((q `1),s)) . (q `2) <= (Meas ((p `1),s)) . (p `2) by A3; :: thesis: verum